A novel in situ stress measurement method based on acoustic emission Kaiser effect: a theoretical and experimental study. Issue 10 (24th October 2018) - Bai, Xin; Zhang, Dong-ming; Wang, Hao; Li, Shu-jian; Rao, Zi
Abstract : Measurement of in situ stress is critical to understand the deformation and destruction of the underground space surrounding rock, and dynamic disaster of the coal mine. At present, with the increasing depth of mining, in situ stress parameters are more and more important for coal mine. In this paper, a novel method for in situ stress measurement with Kaiser effect was studied and applied in the Baijiao coal mine. First, we presented a comprehensive analysis method for the identification of Kaiser effect point. Then, a calculation method for in situ stress measurement based on the Kaiser effect on acoustic emissions was suggested. After that, the in situ stress test of Baijiao coal mine is taken as the research object, an experiment using acoustic emissions monitoring during uniaxial compression testing was performed to investigate the mechanical properties and acoustic emissions characteristics. Finally, in situ stress of the study area was calculated using the novel calculation method above and calculation results were verified using stress relief method and hydraulic fracturing method. The results showed that the calculation results obtained using the proposed method were valid and credible. Therefore, the calculation method for in situ stress measurement and the proposed comprehensive analysis method using the Kaiser point could be applied for in situ stress testing using the Kaiser effect method.